Gap Analysis and Economics of Front Line Demonstrations in Chickpea (Cicer arietinum L.) under Humid South Eastern Plain Zone of Rajasthan - Shivran, R. K.; Kumar, Rajesh; Singh, Ummed; Praharaj, C. S. (International Journal of Bio-resource and Stress Management, 2020)
Performance of improved production technologies of chickpea vis-à-vis farmers’ practice was evaluated through front line demonstrations at farmer’s field during winter seasons starting from October 2007 to April 2008, October 2008 to April 2009 and October 2009 to April 2010 by Agricultural Research Station, Kota. Recommended technologies for the agro-climatic zone developed by the university were adopted in letter and spirit for raising chickpea. Newly released improved varieties of chickpea viz., GNG-663 and GNG-469 were grown under demonstrations. Selection of farmers was done on the basis of Participatory Rural Appraisal (PRA). The results indicated that average yield under improved technology ranged from 1773 to 1907 kg ha-1 with a mean of 1832 kg ha-1. In per cent terms, scaling in productivity following improved technology ranged from 10.20 to 17.74% with an average value of 14.72% (over the Farmers’ practice). The average yield gaps for technology, extension and technology index were 568, 231 kg ha-1 and 12.78%, respectively. Improved technologies also enhanced average gross (Rs. 42,639 ha-1), net return (Rs. 30,087 ha-1), effective gain (Rs. 3,362 ha-1), additional gross (` 5,922 ha-1) and net return (` 4,642 ha-1) in comparison to Farmers’ practice. This resulted in realizing higher incremental cost benefit ratio (4.70) and benefit: cost ratio (3.43) compared to the Farmers’ practice (3.29) during three years study period. This enhancement in grain yield and economics of chickpea under demonstrations clearly showed the impact of adoption of improved technology over farmers’ practice in Humid South Eastern Plain Zone of Rajasthan.